The Experimental Analysis and Behavior of Locally Corroded Metakaolin-Blended Reinforced Concrete Beams Under Flexural Loading - Alamsyah,; Mohd Hanif Ismail,; Ayop, Sallehuddin Shah; Francis George Ambros, (International Journal of Integrated Engineering, 2024)
The deterioration of reinforced concrete (RC) structures, primarily attributed to the corrosion of reinforcement, is significant in constructions situated in coastal areas. Therefore, this experimental study aimed to evaluate the repercussions of corrosion on the flexural strength of RC beams by introducing Metakaolin (MK) to enhance concrete properties including compressive and flexural strength, as well as resistance to chloride penetration. Accelerated corrosion aging techniques were used to induce 10% corrosion in the reinforcing bars embedded in concrete. The corrosion resistance characteristics of longitudinal bars mixed with 10% MK were scrutinized using a half-cell potential test. The actual extent of corrosion in the tensile reinforcement within the 500 mm beam span was determined by extracting the reinforcing bars from the concrete. The parameters evaluated include flexural strength, load-deflection relationship, and failure modes in both uncorroded and corroded RC beams. The results showed that an enhancement in the flexural strength was observed under four-point bending for RC beams corroded with MK compared to those without MK. Additionally, corrosion-induced pitting on the concrete surface led to spalling mechanisms in the beam. These results underscored the positive influence of incorporating MK into concrete, specifically in beams affected by localized corrosion at mid-span. In general, the addition of MK to the concrete mix provided advantages in terms of flexural strength and durability.